Is late adolescence a real risk factor for an adverse outcome of pregnancy?. (17th October 2016) - Ozdemirci, Safak; Kasapoglu, Taner; Cirik, Derya Akdag; Yerebasmaz, Neslihan; Kayikcioglu, Fulya; Salgur, Funda
Abstract: Objective : To compare the obstetrical and neonatal outcomes of late adolescent (LA) and adult pregnancies. Methods : Between January 2012 and December 2012, a total of 313 late adolescent pregnant aged between 16 and 19 years and 418 adult pregnant women aged between 20 and 35 years having given birth in our maternity service were enrolled into this case–control study. The demographic and clinical data were reviewed from hospital database and patients' medical records. Results : The incidence of preterm birth (PB) in the LA group was significantly higher than in the adult group ( p = 0.001), while the incidence of gestational diabetes mellitus was significantly lower ( p = 0.001). The mean birth weight and the rate of delivered macrosomic fetuses in the study group were lower than in the control group ( p = 0.03). The LA group had significantly higher rate of vaginal delivery when compared to the adult group ( p = 0.001). Both the rate of pregnancy induced hypertensive disorders and postpartum hemorrhage were not statistically different between the two groups ( p = 0.31; p = 0.38, respectively). The LA group had lower rate of stillbirth when compared to the adult group; however, the difference was statistically insignificant (0.3% versus 1.2%) ( p = 0.24). Conclusions : The LA pregnancy should be closely followed up during their antenatal care period due to the significantly higher rate of PB.